2015
DOI: 10.1007/s10815-015-0488-0
|View full text |Cite
|
Sign up to set email alerts
|

Unaltered timing of embryo development in women with polycystic ovarian syndrome (PCOS): a time-lapse study

Abstract: The findings suggest that the causative factor for subfertility in PCOS is not related to timing of development in the pre-implantation embryo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 66 publications
2
16
0
Order By: Relevance
“…Previous studies suggested that impaired oocyte and embryo quality could be a concern for decreased reproductive outcomes in women with PCOS (Dumesic and Abbott, 2008;Qiao and Feng, 2011). However, some studies found that there was no causative factor of the pre-implantation embryo for subfertility in PCOS (Sundvall et al, 2015). Our study results showed that the fertilization rate and numbers of viable embryos were comparable between the two groups.…”
Section: Discussionsupporting
confidence: 49%
“…Previous studies suggested that impaired oocyte and embryo quality could be a concern for decreased reproductive outcomes in women with PCOS (Dumesic and Abbott, 2008;Qiao and Feng, 2011). However, some studies found that there was no causative factor of the pre-implantation embryo for subfertility in PCOS (Sundvall et al, 2015). Our study results showed that the fertilization rate and numbers of viable embryos were comparable between the two groups.…”
Section: Discussionsupporting
confidence: 49%
“…The authors believe that predictive models can be very useful, in the first instance for de-selection of embryos undergoing abnormal cleavage events such as direct cleavage and reverse cleavage shown to have a significantly reduced chance of creating a pregnancy (Rubio et al, 2012;Liu et al, 2014) but also, if developed effectively, to select the best embryo from a cohort for a specific patient demographic. Patient characteristics including infertility diagnosis (Sundvall et al,2015) and maternal age (Hampl and Stephan, 2013;Chawla et al, 2015) as well as treatment characteristics including treatment type and culture conditions (Lemmen et al, 2008;Wale and Gardner, 2010;Cirayet al, 2012;Cruz et al, 2013;Kirkegaard et al, 2013b) have been shown to affect an embryo's morphokinetic profile and the resulting subtle differences may be used to identify which embryo has the highest implantation potential. Herein lies a further reason for possible variation in success of TLS between laboratories; patient and treatment characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The present paper presents a multivariate analysis of development in the embryos from 243 patients. Previous publications on the same cohort or subgroups of the cohort have reported on the correlation between early time-lapse parameters and embryo development ( Kirkegaard et al , 2013b ), correlation between metabolism and clinical outcome ( Kirkegaard et al , 2014b ) and development of embryos from women with polycystic ovary syndrome ( Sundvall et al , 2015 ).…”
Section: Methodsmentioning
confidence: 99%